STRATEGI TATUM MENJADI KARAKTERISTIK PEMBINAAN KARAKTER GURU DI SMP IT AL KHAIR KALIMANTAN SELATAN - Noor Khalisatur Rahmah AR; Mohamad Joko Susilo (LPPM UNiversitas Bina Mandiri Gorontalo, 2026)
The TATUM strategy (Talaqqi, Tarbiyah, Ukhuwah, and Mentoring) is a distinctive development model implemented at SMP IT Al Khair, South Kalimantan, which plays a vital role in strengthening teachers’ character while serving as a form of school branding based on Islamic values. This study aims to describe how the implementation of TATUM shapes professional, integrity-driven, and religious teachers who represent the school’s positive image. This research employs a library research method with a descriptive qualitative approach, where data were collected from relevant books, journals, and scientific articles and analyzed using content analysis. The findings reveal that the TATUM strategy functions as a medium for enhancing teachers’ spiritual and professional development through talaqqi and tarbiyah, strengthening solidarity through ukhuwah, and fostering integrity through mentoring activities. With consistent implementation, this strategy successfully builds a religious, collaborative, and quality-oriented school culture while reinforcing the image of SMP IT Al Khair as an integrated Islamic institution that is excellent and characterized by strong moral values